ANALISIS PENGARUH KEPEMILIKAN SAHAM INSTITUSIONAL, KUALITAS AUDIT DAN PENGUNGKAPAN SUKARELA TERHADAP KINERJA KEUANGAN - Suparlan; Nadia Salsabila; Yulis Sunartiana; Desi Intan Berlianawati; Ayu Apriliani (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2024)
This study aims to analyze the effect of institutional share ownership, audit quality, and voluntary disclosure on financial performance in the Basic Materials industry in the Chemicals sub-sector listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. The type of research used is quantitative, with secondary data in the form of company financial reports obtained from the IDX website and related companies. Multiple linear regression analysis is used to test the relationship between the independent variable and the dependent variable. The results showed that institutional share ownership has a significant effect on the company’s financial performance, while audit quality and voluntary disclosure have no significant effect. Overall, supervision by institutional investors can improve the efficiency and profitability of the company, although audit quality and voluntary disclosure have not had a significant effect in the short term.